The treatment of follicular lymphoma with CD19-directed chimeric antigen receptor T-cell therapy - Jacobs, Ryan; Jacobson, Caron (Frontiers in Oncology, 2024)
Follicular lymphoma (FL) is the most common indolent non-Hodgkin lymphoma (NHL). Significant unmet need remains for patients with relapsed/refractory (R/R) FL after ≥3 lines of prior therapy. While recent advancements have likely improved the survival of FL patients, most patients will eventually relapse. The treatment of FL patients after multiple relapses or those with refractory disease has historically led to lower overall response rates (ORR) and shorter progression free survival (PFS) with each subsequent line of therapy. New treatments with high ORR and durable PFS are needed in this setting, particularly in patients that progress within 2 years of first line chemoimmunotherapy (POD24) and/or those refractory chemoimmunotherapy. Chimeric antigen receptor (CAR) T-cell therapies targeting the B-cell antigen CD-19 have shown to be an efficacious treatment option for both heavily pretreated and/or refractory FL patients resulting in a high ORR and durable remissions.